2021
DOI: 10.1063/5.0039963
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fluid flow in MoS2 nanoporous membranes and hydrodynamics interactions

Abstract: We study the impact of the induced pressure fields on the water flow and salt rejection in nanopores produced in MoS 2 membranes. We observe that the water permeability and the salt rejection are not impacted by the distance between the pores. This result contradicts the continuous fluid mechanics calculations in microfilters, which indicates the existence of hydrodynamic interactions between adjacent pores that increase the water mobility. Our results suggest that at this nanoscale, the hydrodynamic interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Figures a and b show water flow rates of the nanopores in the absence of salt ions, and those shown in Figures c and d are for saltwater solutions. For pure water systems, water flow increases linearly with applied pressure which is consistent with results from other authors reported in the literature. ,,,, The flow rates for pure water systems at an applied pressure of 100 MPa are also consistent with those reported by Abal and Barbosa for both pore sizes and all values of charge multiplier …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figures a and b show water flow rates of the nanopores in the absence of salt ions, and those shown in Figures c and d are for saltwater solutions. For pure water systems, water flow increases linearly with applied pressure which is consistent with results from other authors reported in the literature. ,,,, The flow rates for pure water systems at an applied pressure of 100 MPa are also consistent with those reported by Abal and Barbosa for both pore sizes and all values of charge multiplier …”
Section: Resultssupporting
confidence: 91%
“…Thus, the distance between the centers of two neighboring nanopores in the X and Y directions were 3.83 or 3.87 nm, respectively. Some studies suggest that electrostatic coupling between ions in neighboring pores can occur at longer distances. However, a study considering an identical force field and a system very similar to the one utilized in this Article shows that even pores as close as 1.3 nm in distance behave as independent entities with no coupling between salt ions inside the two . That, combined with the low Debye screening length for the ions in the feed reservoir (0.30 nm), indicates that our simulation box is big enough to guarantee no interference between neighboring pores.…”
Section: System Details and Methodsmentioning
confidence: 88%
“…Commonly, a water layer is generated on a smooth surface, but tends to change into disordered bulk-like water with surface roughness, e.g., increasing pore size . Hence, such a hydrodynamic interaction effect is not discerned in MoS 2 nanopores with pore size and interpore distance both at nanoscale, because a thin water layer is formed on the smooth surface of MoS 2 that suppresses such hydrodynamic interactions . However, more attention needs to be paid to the still elusive mechanism of the pore–pore coupling effect at nanoscale in water dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…53 Hence, such a hydrodynamic interaction effect is not discerned in MoS 2 nanopores with pore size and interpore distance both at nanoscale, because a thin water layer is formed on the smooth surface of MoS 2 that suppresses such hydrodynamic interactions. 54 However, more attention needs to be paid to the still elusive mechanism of the pore−pore coupling effect at nanoscale in water dynamics. Additionally, the existence of a water layer is considered to reduce the ion transport rate along the pore axial direction in the atomically thin graphene membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The standard procedure to simulate a water pressure-driven flow in nanoconfined environments is based on the creation of a simulation box with the membrane located between two water reservoirs, , , as shown in Figure a. In order to ensure that the water molecules fill in the membrane, we employ graphene sheets as pistons to control the confined solution pressure.…”
Section: System Details and Methodsmentioning
confidence: 99%